2013
DOI: 10.1016/j.nicl.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Structural abnormalities in cortical volume, thickness, and surface area in 22q11.2 microdeletion syndrome: Relationship with psychotic symptoms

Abstract: Introduction22q11.2 deletion syndrome (22q11DS) represents one of the largest known genetic risk factors for psychosis, yet the neurobiological mechanisms underlying symptom development are not well understood. Here we conducted a cross-sectional study of 22q11DS to decompose cortical volume into its constituent parts, cortical thickness (CT) and surface area (SA), which are believed to have distinct neurodevelopmental origins.MethodsHigh-resolution T1-weighted scans were collected on 65 participants (31 22q11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
106
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 70 publications
19
106
0
Order By: Relevance
“…Differences in global and local GM volumes as well as surface and thickness have been observed in similar regions in 22q11.2 deletion carriers, another largeeffect-size genetic risk factor for psychiatric conditions (49)(50)(51). They are also reminiscent of decreased regional volumes in brain areas associated with emotion and face processing demonstrated in individuals with a 7q11.23 deletion (52,53).…”
Section: Discussionmentioning
confidence: 78%
“…Differences in global and local GM volumes as well as surface and thickness have been observed in similar regions in 22q11.2 deletion carriers, another largeeffect-size genetic risk factor for psychiatric conditions (49)(50)(51). They are also reminiscent of decreased regional volumes in brain areas associated with emotion and face processing demonstrated in individuals with a 7q11.23 deletion (52,53).…”
Section: Discussionmentioning
confidence: 78%
“…However, more interestingly, 30-40% of patients experience high negative symptoms only. Despite their high prevalence, negative symptoms are not yet well characterized in patients with 22q11DS, and the studies investigating the relationship between symptoms severities and psychotic symptoms often referred to positive symptoms only (Jalbrzikowski et al, 2013, Kates et al, 2011, Kunwar et al, 2012.…”
Section: Patients With 22q11ds Manifest Pronounced Negative Symptomsmentioning
confidence: 99%
“…For instance, altered cortical thickness in the orbitofrontal cortex (Jalbrzikowski et al, 2013), volumetric reductions in the temporal lobe (Kates et al, 2011), and reductions in overall gyrification (Kunwar et al, 2012) have been related to positive symptoms in these patients. Cortical thickness reductions in left superior frontal gyrus and in the fusiform and lingual gyri have also been observed in patients with 22q11DS who have been diagnosed with schizophrenia compared to those who have not (Schaer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with 22q11DS show alterations in brain morphology across cortical and subcortical regions, with prefrontal regions relatively preserved [24,25]. Specifically, relative to typically developing controls, 22q11DS patients show reduced cortical volume in occipitoparietal, temporal, and anterior cingulate cortices, and increases in cortical thickness in medial prefrontal regions as well as the insula [24,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, relative to typically developing controls, 22q11DS patients show reduced cortical volume in occipitoparietal, temporal, and anterior cingulate cortices, and increases in cortical thickness in medial prefrontal regions as well as the insula [24,26,27,28]. While total brain volume is typically smaller or not different from controls [25,26,28], Jalbrzikowski et al [24] found increased thickness of the bilateral medial orbitofrontal, middle, and inferior frontal cortices in youth with 22q11DS compared to controls. Mouse models of 22q11DS have shown altered neuronal frequency in layers II/III of the medial prefrontal cortex (PFC), a characteristic that relates directly to performance on tasks of EF [29].…”
Section: Introductionmentioning
confidence: 99%